Pengaruh Kemudahan Penggunaan dan Gender Terhadap Kepuasan Pelanggan Serta Implikasinya Pada Loyalitas Pelanggan - Sari, Nanda Widiya; Amanda, Dea; Sarwoto, Sarwoto; nursaimatussaddiya, Nursaimatussaddiya (Journal of Business and Economics Research (JBE), 2025)
This study aims to examine the extent to which ease of use and gender influence customer satisfaction and its impact on customer loyalty. The research focuses on female teachers who use automatic motorcycles and work at public senior high schools in Tebing Tinggi City. A quantitative approach was applied using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) method, processed through SmartPLS version 4.0. Data were collected through an online questionnaire distributed to 89 respondents. The results indicate that ease of use has a positive and significant effect on both customer satisfaction and loyalty. Gender significantly affects customer loyalty, but not customer satisfaction. Moreover, customer satisfaction does not significantly influence loyalty. Mediation analysis shows that satisfaction does not serve as a mediating variable in the relationship between ease of use and gender toward loyalty. These findings suggest that customer loyalty in this context is more strongly driven by product functionality rather than satisfaction or gender differences.